Genetic mapping of the bd locus - M T Lewis; J F FELDMAN (Fungal Genetics Reports, 1998)
As an initial step toward cloning the band (bd) gene, we sought to pinpoint its genetic location relative to known flanking markers on LGIV prior to initiating a chromosome walk.